On the solvability of a functional Volterra integral equation - El-Sayed, Wagdy G.; Abd El-Rahman, Ragab O.; Abd El-Salam, Sheren A.; El Shahawy, Asmaa A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
In this article, we will investigate the existence of a unique bounded variation solution for a functional integral equation of Volterra type in the space L1(R+) of Lebesgue integrable functions.